Value of 2D ultrasonography in the diagnosis and evaluation of intrauterine adhesions – a prospective study - Huang, Rui; Huang, Xiaowu; Li, Sijing; Zhao, Yuting; Lv, Xiaodan; Li, YingTao; Saravelos, Sotirios; Cheng, Qi; Xia, Enlan; Li, Tin-Chiu (Reproductive biomedicine online, 2024)
•The most frequently encountered 2D ultrasonography feature with intrauterine adhesions (IUA) is irregular endometrium.•Interobserver agreement on the ultrasonographic features of IUA was modestly high.•Ultrasonography diagnosis of IUA using individual features has low sensitivity but high specificity.•With multiple ultrasonographic features, there is an increased likelihood of severe IUA being present. What is the value of 2D ultrasonography in the diagnosis and assessment of intrauterine adhesions (IUA)? This was a prospective study conducted at a hysteroscopy centre. Of a total of 600 subjects recruited, 41 dropped out and 559 were finally enrolled and analysed. The observed 2D ultrasonography features, in decreasing order of frequency, were ‘irregular endometrium’ (37.9%), ‘broken endometrial echo’ (23.4%), ‘thin endometrium’ (13.7%), ‘loss of endometrial echo’ (13.1%,), ‘hyperechoic focus’ (12.5%) and ‘fluid in the cavity’ (8.8%). The sensitivity of individual ultrasound features ranged from 8.8% to 37.9%, whereas the specificity of individual ultrasound features ranged from 78.9% to 100%. When all the six ultrasound features were considered together, the sensitivity and specificity were 71.7% and 66.2% respectively. The sensitivity, specificity and accuracy of ultrasound diagnosis in the mid-proliferative phase, peri-ovulatory phase and mid-luteal phase did not appear to be significantly different statistically, although the results in the mid-proliferative phase appeared to be consistently higher than those in the mid-luteal phase. In women confirmed to have IUA, the likelihood of the adhesions being severe in nature in the presence of zero, one, two or three or more ultrasound features was 8.7%, 23.0%, 40.2% and 80.5%, respectively (P < 0.001). The findings in this study support the notions that ultrasonography examination in women suspected to have IUA cannot replace hysteroscopy in the diagnosis of the condition. However, it does provide useful clinical information regarding severity and could help in the planning of hysteroscopy to optimize management.